Socioeconomic inequalities in health problems in the first two years of life: Pelotas (Brazil) birth cohort, 2015 - Bruno Pereira Nunes; Thaynã Ramos Flores; Vanessa Iribarrem Avena Miranda; Bárbara Heather Lutz; Marília Cruz Guttier; Marysabel Silveira; Andréa Dâmaso Bertoldi (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: Brazil is characterized by an unfinished agenda of health inequalities, which impact health problems in the childhood. This study aimed to evaluate the socioeconomic inequalities of health problems in the early childhood. This is a prospective study, using data from the birth cohort carried out in the city of Pelotas (Rio Grande do Sul State, Brazil) in 2015. The outcomes were health problems presented at 12 and 24 months: cough, breathing difficulty, diarrhea, ear pain, pneumonia, urinary infection, hospitalization, and other health problems. Socioeconomic inequalities were measured applying the slope index of inequality (SII) and the concentration index (CIX), with wealth index and maternal schooling being the socioeconomic variables. The inequalities in the number of health problems were evaluated by Poisson regression. The perinatal sample comprised 4,275 children. At 12 months approximately 74% of the children presented 1 or more health problems, while at 24 months, approximately 44% presented 2 or more health problems. For all period, the mean number of health problems was 2.9 (standard deviation = 2.0). Higher frequencies were observed for children belonging to the poorest income quintile and with lower maternal education, except for 1 or more health problems at 24 months. The greatest absolute and relative inequality was observed for 2 or more health problems at 12 months (SII: -0.23, 95%CI: -0.29; -0.18 and CIX: -0.19, 95%CI: -0.25; -0.14). There is an opposite dose-response relation for the risk of accumulation of health problems according to maternal schooling (1.07, 95%CI: 1.04; 1.09) and wealth categories (1.03, 95%CI: 1.01; 1.04), in the full adjusted models. The study confirms inequalities due to health problems in Brazilian children, especially in the first year of life.